2020
DOI: 10.1371/journal.pone.0239590
|View full text |Cite
|
Sign up to set email alerts
|

Simplified cough test can predict the risk for pneumonia in patients with acute stroke

Abstract: We investigated the association between the results of a simplified cough test and pneumonia onset in 226 patients with acute stroke admitted to Suiseikai Kajikawa Hospital from April to December, 2018. For the simplified cough test, performed on admission, patients orally inhaled a mist of 1% citric acid-physiological saline using a portable mesh nebulizer. When the first cough was evoked or if it remained absent for 30 seconds (indicating an abnormal result), the test was ended. Patients also completed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…The cough reflex is an essential function for protecting and clearing materials that are aspirated into the airway. It has also been reported that the cough test is useful for screening silent aspiration [ 24 ]. The decision of fasting should be done by such an assessment, but not by tongue pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The cough reflex is an essential function for protecting and clearing materials that are aspirated into the airway. It has also been reported that the cough test is useful for screening silent aspiration [ 24 ]. The decision of fasting should be done by such an assessment, but not by tongue pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important airway protective behavior intended to clear penetrant and aspirate material out of the airway in order to maintain a healthy and homeostatic pulmonary environment [3]. Disordered coughing (dystussia) is characterized by reductions in cough airflow, expiratory pressures, and blunted sensorimotor responses [4][5][6][7][8][9] and, when present, is associated with an increased risk of pneumonia [10][11][12][13][14][15].…”
Section: Cough and Dysphagiamentioning
confidence: 99%
“…The recorded data included body mass index (BMI), grip strength, disease duration, alcohol consumption, smoking habits, MDS-UPDRS score [9], medication, Functional Oral Intake Scale (FOIS) score, Eating Assessment Tool-10 (EAT-10) score, and blood test values [13]. Previously reported methods were used to investigate cough re ex, tongue pressure, and peak expiratory ow [14][15][16]. The levodopa equivalent daily dose (LEDD) was calculated according to a recent study [17].…”
Section: Data Acquisitionmentioning
confidence: 99%